Symptomatic and silent cerebral ischemia (detected on MRI) in patients with type 2 diabetes mellitus after carotid revascularization procedures - Marine M. Tanashyan (Endocrinology Research Centre, 2019)
Background: Type 2 diabetes mellitus (T2DM) is a significant independent risk factor for ischaemic stroke. Carotid revascularisation procedures are an effective method of primary and secondary stroke prevention. However, patients developed postoperative acute ischaemic lesions (AILs), which were identified via magnetic resonance imaging (MRI) of the brains. Most of the patients with these AILs lack clinically overt symptoms. Aims: To assess the risk of ischaemic brain damage in patients with T2DM in the setting of carotid angioplasty with stenting (CAS) or carotid endarterectomy (CAE). Materials and methods: This open prospective study comprised of 164 patients with carotid atherosclerosis, who have undergone either CAS or CAE. Patients with T2DM were included in Group 1: 38 patients and 28 patients with CAE. Group 2 included patients without T2DM: 62 patients with CAS and 36 patients with CAE. All patients underwent a thorough neurological examination and diffusion-weighted brain MRI. In patients with T2DM, plasma glucose levels and glycated haemoglobin (HbA1c) were determined and their relationships to brain damage were evaluated. Results: In CAS, there were no statistically significant differences in the AIL frequency in patients with and without T2DM. AILs were found in 15 patients with T2DM (39.8%) and 29 patients without T2DM (46.8%, р = 0.24); three patients without T2DM were diagnosed with stroke. Of the 28 patients with T2DM who underwent CAE, 13 had AIL (46.4%); three had stroke (10.7%). In patients without T2DM, AILs were less prevalent in seven cases (19.4%, р = 0.012) and appeared asymptomatic. Following CAS, the baseline HbA1c levels were higher in patients with T2DM who developed AILs compared to those who did not develop AIL, 7.8% ± 1.4% vs 7.1 ± 1.1% (р = 0.0469). Negative impact of hyperglycaemia on the risk of cerebral ischaemia was observed in patients who underwent CAE, the baseline fasting plasma glucose level was 8.5 ± 1.9 mmol/l vs 7.0 ± 1.5 mmol/l in patients without AIL (р = 0.014). The baseline HbA1c levels in patients with and without AILs were 8.0% ± 1.7% and 6.9% ± 0.9% respectively (р = 0.023). Conclusions: Carotid revascularisation procedure for patients with carotid atherosclerosis may be associated with risk of stroke and asymptomatic acute cerebral ischaemic lesions, which are more prevalent in patients with T2DM. Also, increased HbA1c levels is a risk factor for AIL.